O potencial formativo do livro-reportagem: plano de ataque e os padrões da história narrada pelo jornalismo - Guerreiro, Giovanni Pampolha (2024)
This research was carried out with the aim of investigating the formative potential of the non-fiction novel by adopting Plano de Ataque, by Ivan Sant’Anna, as primary source. To this end, a content analysis was carried out based on textual characteristics of the object, in addition to an interpretation based on what the selected book stimulates. The research proposes a critical outline about traces of the way in which narrative journalism reports historical events like the attacks of September 11th, 2001, using the optics of formation and pseudoformation. The results analyzed through basic concepts of the Critical Theory of Society point to a format with both formative potential, with the understanding that the non-fiction novel is under the logic of the Culture Industry. So, it’s understood that the immanent patterns of the non-fiction novel can be unexplored links between communication and education, objectivity and subjectivity